Pacing strategies and relationships between speed and stroke parameters for elite sprint kayakers in single boats - Goreham, J. A.; Miller, K. B.; Frayne, R. J.; Ladouceur, M. (Journal of Sports Sciences, 2021)
The study aimed to determine the pacing strategies of elite single-boat sprint kayakers, as well as the relationships between stroke parameters (stroke rate (SR) and stroke length (SL)) and kayak speed throughout the race. High-resolution split speed and stroke parameter data from men`s (MK1) and women`s (WK1) single-boat A- and B-finals in 2016-2017 international sprint kayak competitions were analysed. Correlation coefficients were calculated between SR-speed and SL-speed during each split for each race group. Athletes followed all-out, positive and seahorse-shaped pacing strategies for the 200 m, 500 m and 1000 m races, respectively. SL-speed had greater correlations during the first half of the MK1 200 m race, whereas SR-speed had greater correlations during the second half. SR-speed correlations were greater than SL-speed correlations throughout the final 150 m of WK1 200 m races. There were large and very large correlations between SR-speed at the end of both the WK1 500 m and MK1 1000 m race distances, respectively, despite following different pacing strategies. Single-boat pacing strategies change due to race distance during major international sprint kayak competitions, whereas the relationships between stroke parameters and speed change depending on athlete sex and the race distance.